Seleksi Klon Kentang Potensial dan Tanggap terhadap Serangan Organisme Pengganggu Tumbuhan: Selection of Potential Potato Clones and Its Response to Pest and Disease (Jurnal Agroekoteknologi dan Agribisnis, 2022)
The difficulty of obtaining industrial potato varieties that can produce high production and relatively resistant to certain pests and diseases is one of the inhibiting factors for industrial potatoes in Indonesia. The selection of potato clones were expected to produce clones that produce high production and are relatively resistant to certain pests. Twelve potato clones were selected in the Experimental Field of PT. AIMS located at Cinta Village, Karang Tengah District, Garut Regency from May to September 2021. A Randomized Complete Design (RCBD) consisting of twelve treatments and each treatment with five replications were used. The results of the study showed that two clones (Clone–1 and Clone–5) had high yield potential. Clone–1 and Clone–5 produced the highest number of tubers and bulb weights compared to other clones. Clone–5 also showed moderate response to Phytophthora infestants and resistance to Fusarium sp., and show resistance response to insect pests such as Spodoptera litura, Liriomyza sp, and Thrips sp. However, Clone–1 showed a susceptible response to wilt and blight diseases as well as the three species of insect pests. The results of this study concluded to consider the use of Clone–1 and Clone–5 as potato tuber propagation soon.